A atividade das agentes comunitárias de saúde na Estratégia Saúde da Família : entre dramáticas e (re)criações - Sampaio, Renata Oliveira (2016)
This work is the result of studies carried out between the years 2013 and 2015 and intended to analyze the activity of the Community Health Agents (CHA) of two teams of the Family Health Strategy (FHS) in a Health Center located in Nova Rosa da Penha, in the city of Cariacica. To that end, firstly meetings – conversation circles – were held with the CHA to discuss issues relevant to their work: health, prescriptions and activity. In a second moment, an adaptation of the technic of “Instruction to the Look-Alike” was applied and, later, adapted versions of the method of “Simple and Crossed Self-Confrontation”, from Yves Clot. Such propositions contributed in the activity analysis, for they functioned as devices allowing the CHA to produce analyzes about their own activity. These analyzes are discussed in this dissertational work from contributions of the so-called "Work Clinics", using concepts from the Clinic of Activity and the Ergology. Thereby, it was possible to observe the distance between the foregoing standards and the real activity and to know the renormalizations that the CHA operate on the dilemmas experienced at work. We also note that the CHA activity is surrounded by paradoxes ranging from inflation to the lack of standards, from appreciation to devaluation. Thus, we intend that this research will contribute to new ways of thinking / looking at the work of CHA.